Corrosion inhibition in paper and pulp industry by some organic compounds - Quaraishi M.A.; Lal B.; Singh V. (My University, 2025)
Paper industries in India face serious problems due to corrosion of structural components and their high cost of replacement and maintenance. Amongst the wide spectrum of preventive measures available, addition of inhibitors is considered to be a reliable and cost effective means for dealing with corrosion problems. The present investigation aims at evaluation of a few organic compounds, namely lauric hydrazide, undecenoic hydrazide, aniline and para anisidine on corrosion behavior of mild steel in simulated corrosive environment, encountered in paper industries, using weight loss and potentiodynamic methods. © University of Manchester and the authors 2006.